Nature and mode of addition of phosphate precursor in the synthesis of aluminum phosphate and its influence on methanol dehydration to dimethyl ether - Kumar, V. Siva; Padmasri, A. H.; Satyanarayana, C. V. V.; Reddy, I. Ajit Kumar; Raju, B. David; Rao, K. S. Rama (Catalysis Communications, 2006)
Four aluminum phosphate catalysts with Al/P = 1 were prepared by precipitation of mixture of aluminum nitrate and phosphate precursor (either phosphoric acid or diammonium hydrogen phosphate) with NH3 and precipitation of aluminum nitrate with NH3 followed by impregnation of phosphate precursor (either phosphoric acid or diammonium hydrogen phosphate). The catalysts were characterized, using different physico-chemical methods viz., BET-S.A., XRD, FT-IR, and NH3-TPD. Al-27 and P-31 MAS NMR spectroscopy was used to characterize selected catalysts in order to find out the presence of Al and P environments. The catalytic conversion of methanol to dimethyl ether was conducted over these catalysts in a temperature range of 448-548 K at atmospheric pressure. AIPO(4) prepared by precipitating the mixture of aluminum nitrate and (NH4)(2)HPO4 with aq. NH3 generated more number of moderate acid sites and showed higher methanol dehydration activity with 100% selectivity to DME at 548 K. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Al-27 and P-31 MAS NMR; aluminum phosphate; dehydration; dimethyl ether; Methanol; NH3-TPD

Influence of method of preparation on the activity of La-Ni-Ce mixed oxide catalysts for dry reforming of methane - Sagar, T. V.; Sreelatha, N.; Hanmant, G.; Surendar, M.; Lingaiah, N.; Rao, K. S. Rama; Satyanarayana, C. V. V.; Reddy, I. A. K.; Prasad, P. S. Sai (RSC Advances, 2014)
La-Ni-x-Ce1-x mixed oxide catalysts were prepared by a sol-gel method varying the Ni composition (0 <= x <= 1). The catalysts were characterized by X-ray diffraction (XRD), inductively coupled plasma optical emission spectroscopy (ICP-OES), BET surface area, X-ray photoelectron spectroscopy (XPS), temperature-programmed reduction (TPR), H-2 chemisorption and Fourier transform infrared spectroscopy (FT-IR) techniques. CO2 reforming of methane was carried out at atmospheric pressure and 800 degrees C, maintaining a reactant CO2/CH4/N-2 ratio of 80/80/80 (total flow rate = 240 ml min(-1), GHSV of 28 800 h(-1)). The catalysts offered higher activity even at lower Ni compositions. LaNi0.4Ce0.6O3. showed the highest conversion of CH4 and CO2. The H-2/CO ratio in the syngas was stable at 0.85 +/- 0.02. The performance of the sol-gel catalysts was compared with that of the hydrothermally prepared catalysts, reported earlier. High surface area and better Ni dispersion were found to be the reasons for superior activity of the sol-gel catalysts.